A Comparison Study of Operator Preference and Performance for Analog Versus Digital Turbine Control Systems in Control Room Modernization. (3rd April 2019) - Boring, Ronald L.; Ulrich, Thomas A.; Lew, Roger; Kovesdi, Casey R.; Al Rashdan, Ahmad
Abstract: An operator-in-the-loop study was conducted in support of control room modernization for a nuclear power plant. The study featured a benchmark comparison on a glass-top simulator of three variants of a turbine control system (TCS): (1) the existing analog TCS, (2) a proposed stand-alone digital TCS with two displays, and (3) the digital TCS with the addition of a third display consisting of a system overview screen. TCS prototypes were developed to allow formative evaluation of operator preferences and performance during realistic turbine scenarios in the full-scope simulator. The study revealed that completion of turbine startup was several minutes faster with the digital TCS variants than with the conventional analog TCS. Eye-tracking fixations were more widely distributed in the overview versus stand-alone TCS condition, suggesting the overview screen was cueing reactor operators to verify values across the boards. There was no significant difference in workload or situation awareness across the three interfaces. Reviewing key plant parameters showed smoother transitions during load-following for the digital-versus-analog TCS. Despite some performance advantages for the digital TCS variants, operators preferred the existing analog TCS. Open-ended responses suggested this finding may be more an artifact of familiarity than a reflection of dissatisfaction with the new TCS. The study provides compelling evidence that the new digital TCS was used successfully by the operators, suggesting high usability for the digital TCS design. Further advantages were realized through the addition of the system overview screen to provide crews with at-a-glance indicators of key turbine parameters.